Risk and prognosis of secondary malignant neoplasms after radiation therapy for bladder cancer: A large population-based cohort study - Chen, Ru; Zhan, Xiangpeng; Jiang, Haoxin; Liu, Yang; Jiang, Zhi; Jiang, Ming; Deng, Wen; Liu, Xiaoqiang; Chen, Guoxian; Fu, Bin (Frontiers in Oncology, 2022)
Objective: To investigate the association between radiotherapy and the risk of second malignant neoplasms (SMNs) development among patients with bladder cancer (BC). Overall survival (OS) is compared among patients developing SMN and without. Method: We identified patients diagnosed with BC from Surveillance, Epidemiology, and End Results (SEER) database. The development of an SMN is defined as any SMN occurring more than 5 years after the diagnosis of BC. The Fine-Gray competing risk regression is used to estimate the cumulative incidence of SMN. Radiotherapy-associated risk (RR) for SMNs is assessed by Poisson regression. The Kaplan-Meier method was used to evaluate OS of patients with SMNs. Propensity score matching (PSM) is performed. Results: 76575 BC patients are enrolled in our study. The cumulative incidence of SMNs in radiotherapy cohort is statistically higher than non- radiotherapy cohort. In competing risk regression analysis, radiotherapy is proved to associate with a higher risk of SMN (Hazard ratio: 1.23; 95%CI: 1.102-1.368). The radiotherapy-associated risks significantly increase in the radiotherapy cohort (RR: 1.28; 95%CI: 1.14-1.43). In site-specific analysis, statistically significant results are observed in lung and bronchus (LAB) cancer and hematological malignancies. The OS rate in patients developing SMN is significantly lower than that among matched patients with primary BC. Conclusion: Radiotherapy for BC is associated with SMN. Radiotherapy increases the risk of secondary low-dose area cancer development, including LAB cancer or hematological malignancies. Notably, this effect is not observed in the high-dose area involving pelvic tumors. Patients developing SMN showed poorer OS.